Marker Aided Incorporation of Saltol, a Major QTL Associated with Seedling Stage Salt Tolerance, into Oryza sativa ‘Pusa Basmati 1121’ - Babu, N. Naresh; Krishnan, S. Gopala; Vinod, K. K.; Krishnamurthy, S. L.; Singh, Vivek K.; Singh, Madan P.; Singh, Renu; Ellur, Ranjith K.; Rai, Vandna; Bollinedi, Haritha; Bhowmick, Prolay K.; Yadav, Ashutosh K.; et al. (Frontiers in Plant Science, 2017)
Pusa Basmati 1121 (PB1121), an elite Basmati rice cultivar is vulnerable to salinity at seedling stage. A study was undertaken to impart seedling-stage salt tolerance into PB1121 by transferring a quantitative trait locus (QTL), Saltol, using FL478 as donor, through marker assisted backcrossing. Sequence Tagged Microsatellite Site (STMS) marker RM 3412, tightly linked to Saltol was used for foreground selection. Background recovery was estimated using 90 genome-wide STMS markers. Systematic phenotypic selection helped in accelerated recovery of recurrent parent phenome. A set of 51 BC3F2 lines homozygous for Saltol were advanced to develop four improved near isogenic lines (NILs) of PB1121 with seedling stage salt tolerance. The background genome recovery in the NILs ranged from 93.3 to 99.4 per cent. The improved NILs were either similar or better than the recurrent parent PB1121 for yield, grain and cooking quality and duration. Biochemical analyses revealed significant variation in shoot and root Na+ and K+ concentrations. Correlation between shoot and root Na+ concentration was stronger than that between root and shoot K+ concentration. The effect of QTL integration into the NILs was studied through expression profiling of OsHKT1;5, one of the genes present in the Saltol region. The NILs had significantly higher OsHKT1;5 expression than the recurrent parent PB1121, but lower than FL478 on salt exposure validating the successful introgression of Saltol in the NILs. This was also confirmed under agronomic evaluation, wherein the NILs showed greater salt tolerance at seedling stage. One of the NILs, Pusa1734-8-3-3 (NIL3) showed comparable yield and cooking quality to the recurrent parent PB1121, with high field level seedling stage salinity tolerance and shorter duration. This is the first report of successful introgression of Saltol into a Basmati rice cultivar.